2019
DOI: 10.1093/jrs/fez023
|View full text |Cite
|
Sign up to set email alerts
|

‘You can’t have a good integration when you don’t have a good communication’: English-language Learning Among Resettled Refugees in England

Abstract: The research presented here is based on a large scale, multi-methods study of refugees who have been resettled to the UK. We analyse quantitative data on language proficiency four or more years after resettlement to identify the key characteristics of those who are most likely to have low language proficiency and to be at risk of long term dependency and exclusion. Qualitative interviews on experiences of language learning suggest that English language policy and provision serves to exacerbate and compound the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Anyway, only two countries worldwide actually provide freely available language courses for migrants upon arrival (Sweden and Canada) [72]. Recently, Morrice and colleagues published an interesting article entitled "You cannot have a good integration when you do not have a good communication" [73]. We would like to readopt this concept and say that "you cannot have good mental health if you do not have a good communication."…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, only two countries worldwide actually provide freely available language courses for migrants upon arrival (Sweden and Canada) [72]. Recently, Morrice and colleagues published an interesting article entitled "You cannot have a good integration when you do not have a good communication" [73]. We would like to readopt this concept and say that "you cannot have good mental health if you do not have a good communication."…”
Section: Discussionmentioning
confidence: 99%
“…However, research has shown that too often refugees are treated as a homogeneous group and there are not the tailored pathways in place to enable individuals to access language and employment support appropriate to their needs. For example, refugees arriving with professional backgrounds would benefit from fast track language courses combined with vocational skills which would support faster access to employment commensurate with their background and qualifications (Morrice et al 2019). This is reflected in the themes emerging from the qualitative data, which showed that barriers to gaining employment and learning the language undermined mastery experiences and negatively influenced individuals' physical and emotional states (and thereby their self-efficacy and positive affect).…”
Section: Discussion: Self-efficacy Predicts Positive Affectmentioning
confidence: 99%
“…English language skills have been shown to impact wellbeing of refugees in the UK in various ways (e.g. Morrice et al 2019;Tip et al 2019), and the interviews revealed how self-efficacy may play a role in this link. Immediately after the support provided by the Gateway Programme ended, which was one year after arrival, some people felt that they were unable to address problems they faced in their daily lives in the UK.…”
Section: Rasul Iraqmentioning
confidence: 99%
“…40 See http://iamamigrant.org/stories/cambodia/sophal. On the importance of and barriers to language learning for refugees, see Morrice et al, 2019. 41 Chiswick, 2016Aoki and Santiago, 2018.…”
Section: Languagementioning
confidence: 99%